PENGARUH PEMBERIAN EKSTRAK BUAH PIDADA MERAH (Sonneratia caseolaris) TERHADAP KADAR KOLESTEROL TOTAL TIKUS GALUR WISTAR DIABETIK - Putri Maria Grace Bintang (2023)
Dyslipidemia in diabetes is related to cardiovascular disorders which cause the highest mortality in Indonesia. Alternative medicine using red pidada fruit (Sonneratia caseolaris) contains flavonoids, triterpenoids, phenolics, alkaloids, saponins, and tannins. The purpose of the research was to find out the effect of giving red pida fruit extract (EBPM) on total cholesterol levels in diabetic Wistar rats. A real research design with a pre-test and post-test control group design. A sample Rattus norvegicus Wistar strain 30, male, 150-200 grams, 2-3 months, given high fat feed for 28 days. After fasting for 10 hours, alloxan 125 mg/kgBW was given intraperitoneally. After 3 days, take blood from the tail to check total cholesterol with a spectrophotometer (λ = 546 nm). Rats were grouped into group 1 (standard feed, aquades), group 2 (alloxan), group 3 (alloxan, simvastatin), and groups 4, 5, 6 (alloxan, EBPM dose (200; 400; 800) mg/kgBW), treatment for 14 days, then terminated with ketamine xylazine, take blood and put it in an EDTA tube, check total cholesterol. One way ANOVA test results have effect of EBPM on total cholesterol levels (p=0,001) and Bonferroni post hoc results have a significant difference with the negative control, but not with the positive control (p=1,000). Red kidney extract has an effect on total cholesterol with the best concentration of 200 mg/kgBB.